Status and outlook of sensitizers/dyes used in dye sensitized solar cells (DSSC): a review. (24th April 2016) - Shalini, S.; Balasundaraprabhu, R.; Kumar, T. Satish; Prabavathy, N.; Senthilarasu, S.; Prasanna, S.
Summary: Dye‐sensitized solar cells (DSSCs) have become a topic of significant research in the last two decades because of their scientific importance in the area of energy conversion. Currently, DSSC is using inorganic ruthenium (Ru)‐based, metal‐free organic dyes, quantum‐dot sensitizer, perovskite‐based sensitizer, and natural dyes as sensitizer. The use of metal‐free, quantum‐dot sensitizer, perovskite‐based sensitizer, and natural dyes has become a viable alternative to expensive and rare Ru‐based dyes because of low cost, ease of preparation, easy attainability, and environmental friendliness. Most of the alternatives to Ru‐based dyes have so far proved inferior to the Ru‐based dyes because of their narrow absorption bands (Δ λ ≈ 100–250 nm), adverse dye aggregation, and instability. This review highlights the recent research on sensitizers for DSSC, including ruthenium complexes, metal‐free organic dyes, quantum‐dot sensitizer, perovskite‐based sensitizer, mordant dyes, and natural dyes. It also details and tabulates all types of sensitizer with their corresponding efficiencies. Plot of progress in efficiency ( η ) of DSSC till date based on different types of sensitizers is also presented. Copyright © 2016 John Wiley & Sons, Ltd. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The recent research on sensitizers for DSSC, including ruthenium complexes, metal‐free organic dyes, quantum‐dot sensitizer, perovskite‐based sensitizer, mordant dyes, and natural dyes is presented. All type of sensitizers with their corresponding efficiencies is tabulated. Plot of progress in efficiency (η) of DSSC till date based on different types of sensitizers is also presented.